ATTITUDES OF THE ESTONIAN BORDER GUARD AND POLICE OFFICERS ON IMMIGRATION AND RADICALIZATION - Veispak-Rawlings, Kai (Border Security and Management, 2020)
The article in the first part outlines the current discussion of the state of training under cultural intelligence, including definitions and examples of possible interdictions of the bad players. The second part describes the attributes and attitudes of Border Guard and Police officers after cultural intelligence courses, defining and applying the concepts towards internal security with a focus on Cultural Identity, “what makes a person tick.” An empirical study consisting of written reports was conducted over a three-year period and compiled to reflect attitudes towards immigration and radicalization in the EU.